MRI and clinical findings in patients with ankylosing spondylitis eligible for anti-tumour necrosis factor therapy after a short course of etoricoxib. Issue 9 (24th October 2008) - Jarrett, S J; Sivera, F; Cawkwell, L S; Marzo-Ortega, H; McGonagle, D; Hensor, E; Coates, L; O'Connor, P J; Fraser, A; Conaghan, P G; Emery, P
Abstract : Objective: To describe and assess the response to short-term etoricoxib as shown by MRI and clinical variables in patients with ankylosing spondylitis (AS) selected for eligibility for anti-tumour necrosis factor therapy. Methods: In a 6-week open-label study, 22 patients with AS and eligible for biological therapy were treated with 90 mg of etoricoxib daily. Clinical and laboratory parameters were obtained and MRI of the sacroiliac joints and the lower thoracic and lumbar spine performed at baseline and at week 6. The primary end point was the proportion of patients fulfilling the SpondyloArthritis international Society (ASAS) response criteria for biological therapies (ASASBIO) while secondary end points included the change in MRI-determined bone lesions. Results: Eight of 20 completers improved enough to meet the ASASBIO response criteria and most clinical variables improved significantly. Fifteen patients had a total of 63 MRI-detectable lesions; overall, 13/60 lesions with paired scans either resolved completely or improved, while five lesions worsened or appeared during treatment. Conclusion: Etoricoxib is an effective symptomatic treatment for patients with AS; however, its effect on MRI-detected lesions is small. Further studies are needed to determine the effect of etoricoxib on MRI-determined bone oedema.